Essential quality parameters of commercial Virgin Coconut Oil - Fabian M. Dayrit; Olivia Erin M. Buenafe; Edward T. Chainani; Ian Mitchelle S. de Vera; Ian Ken D. Dimzon; Estrella G. Gonzales; Jaclyn Elizabeth R. Santos (International Coconut Community Journal, 2007)
Chemical analyses conducted on commercial samples of virgin coconut oil (VCO) produced by four different methods gave the following ranges of values: % Fatty acid composition: C6: 0.24 to 0.49%; C8: 4.15 to 8.30%; C10: 4.27 to 5.75%; C12: 46.0 to 52.6%; C14: 16.0 to 19.7%; C16: 7.65 to 10.1%; C18: 2.86 to 4.63%; C18:1: 5.93 to 8.53%; C18:2: 1.00 to 2.16%; % moisture by Karl Fischer: 0.05 to 0.12%; % matter volatile at 120°C: 0.12 to 0.18%; %free fatty acids as lauric acid: 0.042 to 0.329%; and peroxide value: none detected to 1.40. The tests for % moisture by Karl Fischer and % matter volatile at 120°C can be used to differentiate VCO from and refined, bleached and deodorized coconut oil (RBD CNO). No trans-fatty acid was detected in both VCO and RBD CNO down to 0.01% (w/w) detection limit.